2022
DOI: 10.1101/2022.09.22.509045
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparison Between Gradients and Parcellations for Functional Connectivity Prediction of Behavior

Abstract: Resting-state functional connectivity (RSFC) has been widely used to predict behavioral measures. To predict behavioral measures, there are different approaches for representing RSFC with parcellations and gradients being the two most popular approaches. There is limited comparison between parcellation and gradient approaches in the literature. Here, we compared different parcellation and gradient approaches for RSFC-based prediction of a broad range of behavioral measures in the Human Connectome Project (HCP)… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 85 publications
1
9
0
Order By: Relevance
“…In fact, parcellations of different resolutions are likely useful for different applications. For example, behavioral prediction generally improves with higher dimensional parcellations before plateauing or becoming worse, although the exact results can be quite variable across studies (Dadi et al, 2019; Pervaiz et al, 2020; Kong et al, 2022). On the other hand, a recent study has suggested that brain–behavior relationships are scale-dependent (Betzel et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, parcellations of different resolutions are likely useful for different applications. For example, behavioral prediction generally improves with higher dimensional parcellations before plateauing or becoming worse, although the exact results can be quite variable across studies (Dadi et al, 2019; Pervaiz et al, 2020; Kong et al, 2022). On the other hand, a recent study has suggested that brain–behavior relationships are scale-dependent (Betzel et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Recent work has recognized the need for massive numbers of subjects to reliably associate brain phenotypes with behavior, specifically in developmental RSFC (Marek et al, 2022). This could be attributed to the complexity of neuroimaging phenotypes, but by leveraging machine learning advances like multivariate models, functional alignment, and individualized atlases, we can improve prediction (Dubois and Adolphs, 2016; Kong et al, 2019, 2021, 2023; Rosenberg et al, 2020; Feilong et al, 2021, 2022; Chen et al, 2022; DeYoung et al, 2022). We demonstrate hyperalignment’s power as a tool for understanding developing brain–behavior associations.…”
Section: Discussionmentioning
confidence: 99%
“…While computing connectivity profiles to be hyperaligned, it is often desirable to use individualized connectivity targets to account for topographic idiosyncrasies in target regions. Individualized connectivity targets can be generated with individualized parcellations (Glasser et al, 2016; Langen et al, 2018; Kong et al, 2019, 2021, 2023; Anderson et al, 2021) or by iterating the hyperalignment algorithm (Busch et al, 2021; Jiahui et al, 2023). In our implementation for this study, we used parcels from the Glasser cortical parcellation (Glasser et al, 2016) as the cortical fields and targets to be hyperaligned.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Others have identified changes in gradient range in response to changing states or task demands (Brown et al, 2022; Cross et al, 2021; Gale et al, 2022; Murphy et al, 2019; Shao et al, 2022; Zhang et al, 2022). Still others have leveraged regional values from one or more FC gradients to predict various behavioral features in multivariate analyses (Bethlehem et al, 2020; Hong et al, 2020; Kong et al, 2022).…”
Section: Introductionmentioning
confidence: 99%